Formation and Characterization of the Boron Dicarbonyl Complex [B(CO)2]−. (14th September 2015) - Zhang, Qingnan; Li, Wan‐Lu; Xu, Cong‐Qiao; Chen, Mohua; Zhou, Mingfei; Li, Jun; Andrada, Diego M.; Frenking, Gernot
Abstract We report the synthesis and spectroscopic characterization of the boron dicarbonyl complex [B(CO)2]−. The bonding situation is analyzed and compared with the aluminum homologue [Al(CO)2]− using state‐of‐the‐art quantum chemical methods.